Sensory characteristics of Garcinia mangostana stored in refrigerated and environmental conditions (Agroindustrial Science, 2022)
The mangosteen is a tropical fruit for which there is little information on consumer acceptability in Ecuador. Therefore, this research aimed to study Garcinia mangostana in a sensory manner stored in refrigerated (5 ± 1 °C) and environmental (18 ± 2 °C) conditions. This study was carried out with fruits harvested from 20-year-old plants, which were stored in cardboard boxes under the established conditions. The statistical program InfoStat was used for the non-parametric Friedman analysis of variance (p-value < 0.05) of the data obtained in the variables that were established under a randomized complete block design (DBCA), with a total of nine treatments in each of the three replications. For the sensory evaluation, a group of different panelists was summoned for each storage time (0, 7, 14, 21, 28 days), which gave a rating to each of the variables (appearance, smell, color and taste) on a hedonic scale from 1 to 5. The results showed that for the panelists, the taste was more pleasant in the fruits stored in refrigeration, while the rest of the variables had similar scores.
Keywords: Tasting; fresh fruit; mangosteen; panelists; preferences